IDENTIFICATION AND VERIFICATION OF VEHICLE DRIVE AND STEERING PERFORMANCE. Issue 1 (July 2021) - Zhu, Baoquan; Lin, Ying; Zhao, Qiang; Du, Ying; Yu, Lele
Abstract: Through the analysis of vehicle driving characteristics and steering dynamics, the system identification of vehicle driving performance and steering performance and the identification of driver types are obtained. Using MATLAB software, by analyzing the relationship between speed and engine speed, the specific gear selected by the driver at a certain time is determined, and the throttle percentage and speed amplitude-frequency characteristic curve of the gear are estimated by TFESTIMATE. The driving characteristics of each gear of the experimental vehicle are obtained. According to the values of steering wheel angle, vehicle lateral acceleration and real-time speed, the corresponding law of vehicle lateral acceleration changes and steering wheel angle changes under different speed is obtained by using transfer function identification.